The involvement of post-translational modifications in cardiovascular pathologies: Focus on SUMOylation, neddylation, succinylation, and prenylation. (January 2020) - Gao, Jinning; Shao, Kai; Chen, Xiatian; Li, Zhe; Liu, Ziqian; Yu, Zhongjie; Aung, Lynn Htet Htet; Wang, Yin; Li, Peifeng
Abstract: Cardiovascular disease (CVD) is one of the most threatening diseases to human health and life, and the number of patients is increasing year by year. Thus, it is of great significance to study the pathogenesis, prevention and treatment of CVDs. The occurrence and development of CVDs involve dynamic, complex and delicate intracellular processes and the pathogenesis is not entirely clear. In contrast to genetic mutations, most of the protein post-translational modifications (PTMs) are reversible, and can affect the activity, stability, subcellular localization, protein-protein interaction etc., of the substrate targets, emerging as key mediators of a number of CVD progression. Under pathological conditions, the PTMs undergo aberrant balances which cause changes of the substrate target proteins in expression level, localization and capacity to activate downstream signaling pathways. Therefore, new approaches can be created aiming to correct the abnormal PTM alterations in treating CVDs. This review summarizes some of the more recent advances in PTMs, focusing on SUMOylation, neddylation, succinylation, and prenylation, and the effect of these modifications on cardiovascular function and progression, which may provide potential targets for future therapeutics. Highlights: Protein post-translational modifications play remarkable roles in cardiovascular pathologies. SUMOylation plays important role in apoptosis, cardiac hypertrophy and fibrosis by regulating multiple signaling pathways. Neddylation mediates heart development by repressing Hippo kinases and activating YAP signaling. SIRT5-mediated desuccinylation and regulation of SDH during IR injury in heart. These PTMs may provide potential targets and novel therapeutic strategies in cardiology.